Increased Expressions of Programmed Death Ligand 1 and Galectin 9 in Transplant Recipients Who Achieved Tolerance After Immunosuppression Withdrawal. Issue 4 (10th November 2021) - Hai Nam, Nguyen; Taura, Kojiro; Koyama, Yukinori; Nishio, Takahiro; Yamamoto, Gen; Uemoto, Yusuke; Kimura, Yusuke; Xuefeng, Li; Nakamura, Daichi; Yoshino, Kenji; Ogawa, Eri; Okamoto, Tatsuya; et al.
Abstract : Programmed death 1 (PD1)/its ligand PD‐L1 concomitant with T cell immunoglobulin and mucin domain‐containing protein 3 (TIM‐3)/its ligand galectin 9 (Gal‐9) and the forkhead box P3 (FOXP3) might be involved in tolerance after liver transplantation (LT). Liver biopsies from 38 tolerant, 19 nontolerant (including 16 samples that triggered reintroduction of immunosuppression [IS] and 19 samples after IS reintroduction), and 38 control LT patients were studied. The expressions of PD1, PD‐L1, Gal‐9, and FOXP3 were determined by immunohistochemical and immunofluorescence (IF) staining. The success period of IS withdrawal was calculated using Kaplan‐Meier curve analysis. Tolerant and control patients exhibited higher PD‐L1, Gal‐9, and FOXP3 levels than nontolerant patients at the moment of triggering IS reintroduction. High expressions of PD‐L1 and Gal‐9 were associated with prolonged success of tolerance (83.3% versus 36.7% [ P < 0.01] and 73.1% versus 42.9% [ P = 0.03]). A strong correlation between PD‐L1 and Gal‐9 expression levels was detected (Spearman r = 0.73; P ≤ 0.001), and IF demonstrated colocalization of PD‐L1 and Gal‐9 in the cytoplasm of hepatocytes. In conclusion, the present study demonstrated that increased expressions of PD‐L1 and Gal‐9 were associated with sustained tolerance after IS withdrawal in pediatric liver transplantation.